Characterization of hematopoietic stem cell subsets from patients with multiple myeloma after mobilization with plerixafor - Hoffmann, Isabel; Saffrich, Rainer; Zepeda-Moreno, Abraham; Hellwig, Isabelle; Eckstein, Volker; Bruckner, Thomas; Ho, Anthony Dick; Wuchter, Patrick (Cytotherapy, 2011)
Background aims - Previous studies have demonstrated that the combination of granulocyte-colony-stimulating factor (G-CSF) + plerixafor is more efficient in mobilizing CD34+ hematopoietic stem cells (HSC) into the peripheral blood than G-CSF alone. In this study we analyzed the impact of adding plerixafor to G-CSF upon the mobilization of different HSC subsets. - Methods - We characterized the immunophenotype of HSC subsets isolated from the peripheral blood of eight patients with multiple myeloma (MM) before and after treatment with plerixafor. All patients were supposed to collect stem cells prior to high-dose chemotherapy and consecutive autologous stem cell transplantation, and therefore received front-line mobilization with 4 days of G-CSF followed by a single dose of plerixafor. Samples of peripheral blood were analyzed comparatively by flow cytometry directly before and 12h after administration of plerixafor. - Results - The number of aldehyde dehydrogenase (ALDH)bright and CD34+ cells was significantly higher after plerixafor treatment (1.2-5.0 and 1.5-6.0 times; both P <0.01) and an enrichment of the very primitive CD34+ CD38− and ALDHbright CD34+ CD38− HSC subsets was detectable. Additionally, two distinct ALDH+ subsets could be clearly distinguished. The small ALDHhigh subset showed a higher number of CD34+ CD38− cells in contrast to the total ALDHbright subpopulation and probably represented a very primitive subpopulation of HSC. - Conclusions - A combined staining of ALDH, CD34 and CD38 might represent a powerful tool for the identification of a very rare and primitive hematopoietic stem cell subset. The addition of plerixafor mobilized not only more CD34+ cells but was also able to increase the proportion of more primitive stem cell subsets.